Brain metastases in endometrial cancer: A systematic review of the surgical prognostic factors. (March 2021) - Beucler, Nathan; Sellier, Aurore; Bernard, Cédric; Joubert, Christophe; Desse, Nicolas; Dagain, Arnaud
Abstract: Context: Although endometrial cancer is the fourth most common malignancy in women, dissemination to the brain is an exceptional event in the course of the disease. The aim of this review is to determine the important surgical prognostic factors for patients with endometrial cancer metastatic to the brain. Materials and methods: Report of two cases. Medline database was used to conduct a systematic literature review from inception to December 2020 looking for English-language articles focused on brain metastases from endometrial cancer. Results: The research yielded 108 articles, among which 23 articles were retained for a total of 87 patients. Mean age was 60 years-old ±11 at the time of diagnosis of endometrial cancer, and most of the tumors were aggressive (grade 3) with an advanced-stage disease (FIGO III-IV). At the time of diagnosis of cerebral disease, a single brain metastasis (p < 0.0001) and no extra-cerebral metastatic site (p = 0.0011) were significant good prognostic factors for the median overall survival. Surgical excision of brain metastasis followed by radiotherapy provided the longest median overall survival compared to radiotherapy and/or chemotherapy, and surgery alone (respectively 32, 5.4 and 4.8 months, p < 0.0001). An age of 60-year-old or less was not associated with a better prognosis. Conclusion: This review confirms that surgical excision followed by radiotherapy is a reliable option in patients with a single brain metastasis from endometrial cancer and no extra-cerebral metastatic site. This work could help to adapt the Graded Prognostic Assessment for brain metastases in endometrial cancer.